Practice ecology of sustainable travel: The importance of institutional policy-making processes beyond the traveller. (April 2019) - Williams, David G.; Spotswood, Fiona; Parkhurst, Graham; Chatterton, Tim
Highlights: Paper combines 3 Elements Model, with Systems of Provision model. Model shows how central government influenced local authority grant bidding practices. Meanings travel from central government and influence the type of schemes delivered. Funding identified as a means of exerting government power within this system. Model enhances policy-maker understanding of the wider impacts of interventions. Abstract: Changing mobility behaviour towards activities and actions that have a less detrimental impact on the environment, public health and society is an objective of transport policy jurisdictions globally. In line with a burgeoning body of research examining behaviour and social change, this paper explores the governmental systems that influence mobility behaviours through a social practice lens. This paper blends two social practice theoretical models, the '3-Elements Model' and 'Systems of Provision', as a means of understanding the delivery of the Local Sustainable Transport Fund (LSTF), a central government grant scheme for English local authorities. We examine how the meanings, materials and competences within the practices of bid writing by local authorities and scheme selection by government influenced the distribution of funding to local authorities. The research starts from the principle that, where funding is provided by central government, in the case of this research that of the UK, an opportunity is created for mobility practices to change. The significance of funding is not easily theorised by the 3-Elements model but is more helpfully explained when that model is blended with the wider Systems of Provision model to create a model of practice ecology. Our theorisation allows for a rigorous exploration of the 'practice scaffolding' which shapes how people travel. Policymakers are recommended to consider a practice ecology approach when developing mobility management schemes to tackle air quality, climate change and obesity issues more effectively.